Salp swarm algorithm to combined economic and emission dispatch problems - Bestha, Mallikarjuna; V. Siva Reddy, Y; Kiranmayi, R (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to present a Salp Swarm (SS) Algorithm for the solution of Combined Economic Emission Dispatch (CEED) problem. The production of electricity from the thermal power generation plants releases large containments of oxides of Nitrogen (NOx), Sulphur (SOx) and Carbon (COx) into the atmosphere. The CEED problem has been treated as a bi-objective optimization problem by taking economic and emissions simultaneously. SS algorithm is a recently suggested optimization algorithm based on swarming behaviour of salps when foraging and navigating in the oceans. To verify the robustness of the suggested SS algorithm is tested for CEED of two test systems with losses. All the results are carried out to demonstrate the effectiveness and validity of the scheme for practical applications. These study results have shown that the approach developed is efficient and suitable for real-time applications.Â Â